Perancangan Dan Implementasi Bot Telegram Untuk Pemetaan Lokasi ODP Dan Akses Informasi Di Telkom Akses Kota Samarinda - Alvin Hakim; Tranggono Tranggono (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
Facing the dynamic landscape of the telecommunications industry, this research delves into key challenges in the operational efficiency of network management. The approach involves designing and implementing an innovative Telegram bot, specifically crafted to map the locations of Optical Distribution Points (ODP). This bot enables technicians to easily access information by entering the ODP name through the Telegram platform. The research methodology employs a descriptive method and a development method using the waterfall SDLC (Software Development Life Cycle) concept, suitable for small-scale projects. Unified Modeling Language (UML), including Use Case Diagrams and Activity Diagrams, aids in the system design. The author conducted an in-depth identification of field technicians' requirements, storing ODP data in Google sheets, including ODP name, geographical coordinates, address, partner, (GPON), and status. The Telegram bot implementation displays location information linked directly to Google Maps, providing essential details such as address, partner, type (GPON), and ODP status. This Telegram bot implementation demonstrates a significant positive impact, contributing to the effectiveness and empowerment of field technicians in managing ODP data. Discussions involving bot success evaluation and potential work effectiveness underscore positive outcomes. The research anticipates that all technicians at PT Telkom Akses Samarinda can utilize this bot to enhance their operational workflows.